Flexibility and Control of Circadian Activity, Migratory Restlessness and Fueling in Two Songbird Migrants - Åkesson, Susanne; Ilieva, Mihaela; Bianco, Giuseppe (Frontiers in Ecology and Evolution, 2021)
Juvenile songbirds rely on an endogenous program, encoding direction, distance, fuelling, and timing of migration. Migratory distance is species-specific, expressed as a period of migratory restlessness, for which the length is correlated with distance, while fuelling is modified to meet anticipated flight distances controlled by geomagnetic cues and amount of day-light available for foraging. How daylength affect onset and level of migratory activity and fuelling decisions in wild birds have so far received limited attention. Here we study how photoperiod controls onset, level and extent of autumn migratory activity and fuelling in juvenile diurnally migrating dunnocks, and nocturnally migrating European robins by experimentally increasing daylength. For both species, we kept a control group indoors at the location of capture in southern Sweden exposed to the natural photoperiod, and an experimental group with increased and advanced photoperiod by two hours in the morning. Dunnocks initiated migratory activity at sunrise (or artificial sunrise) in both groups, demonstrating a highly responsive and flexible component for the onset of migration triggered by light. Experimental robins anticipated the end of nocturnal migratory activity predicting the earlier sunrise immediately after the time-shift and expressed this behaviour already under darkness, supporting a fast-resetting mechanism to the new diel period. Timing of end of morning activity was not affected by the earlier sunrise in both species, suggesting a fixed endogenous control that persisted throughout the 13-day study period. Experimental dunnocks expressed higher overall activity and lower fuel loads than controls, while robins did not change their overall activity and fuel load in response to the shifted and increased photoperiod. These results reveal important adaptations for circadian timekeeping including both a flexible onset open to fast modifications and a more rigid end, with differential effects by the treatment on migratory activity and fuelling in the two species.